NC-MACPABE: Non-centered multi-authority proxy re-encryption based on CP-ABE for cloud storage systems - Xu, Xiao-long; Zhang, Qi-tong; Zhou, Jing-lan (Journal of Central South University, 2017)
The cloud storage service cannot be completely trusted because of the separation of data management and ownership, leading to the difficulty of data privacy protection. In order to protect the privacy of data on untrusted servers of cloud storage, a novel multi-authority access control scheme without a trustworthy central authority has been proposed based on CP-ABE for cloud storage systems, called non-centered multi-authority proxy re-encryption based on the cipher-text policy attribute-based encryption (NC-MACPABE). NC-MACPABE optimizes the weighted access structure (WAS) allowing different levels of operation on the same file in cloud storage system. The concept of identity dyeing is introduced to improve the users’ information privacy further. The re-encryption algorithm is improved in the scheme so that the data owner can revoke user’s access right in a more flexible way. The scheme is proved to be secure. And the experimental results also show that removing the central authority can resolve the existing performance bottleneck in the multi-authority architecture with a central authority, which significantly improves user experience when a large number of users apply for accesses to the cloud storage system at the same time.